2012
DOI: 10.1111/j.1751-7176.2012.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Endothelial Microparticles and Their Correlation With the Presence of Hypertension and Arterial Stiffness in Patients With Type 2 Diabetes

Abstract: Microparticles (MPs) are associated with several cardiovas-cular complications. As multifunction biomarkers, they may contribute to the pathogenesis of diabetes-associated vas-cular diseases. A total of 39 patients with diabetes and hypertension, 24 patients with diabetes without hyper-tension, and 20 healthy controls were enrolled. Flow cytometry was applied to detect plasma MPs, including endothelial MPs (EMPs), annexin V+MPs, platelet-derived MPs (PMPs), and leukocyte-derived MPs (LMPs). Brachial ankle puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 19 publications
3
38
0
Order By: Relevance
“…The timecourse for reductions in 2 EMV may therefore not always mirror reductions in body mass. Hypertension is 3 associated with elevated EMV (Chen et al, 2011), consistent with the mechanosensitive 4…”
mentioning
confidence: 83%
“…The timecourse for reductions in 2 EMV may therefore not always mirror reductions in body mass. Hypertension is 3 associated with elevated EMV (Chen et al, 2011), consistent with the mechanosensitive 4…”
mentioning
confidence: 83%
“…These findings suggest that microparticles from EPCs and endothelial cells could be used as predictive biomarkers for ischemic stroke complication in diabetes, and targeting microparticles might offer new therapeutic avenues for diabetes and ischemic stroke. Levels of endothelial-derived, but not leukocyte-derived, microparticles are higher in hypertensive diabetic patients than in those without hypertension [23]. Endothelial-derived microparticles were shown to be an independent risk factor for the presence of hypertension in diabetic patients [23].…”
Section: Microparticles Are Biomarkers For Cardiovascular Pathologiesmentioning
confidence: 99%
“…Levels of endothelial-derived, but not leukocyte-derived, microparticles are higher in hypertensive diabetic patients than in those without hypertension [23]. Endothelial-derived microparticles were shown to be an independent risk factor for the presence of hypertension in diabetic patients [23].…”
Section: Microparticles Are Biomarkers For Cardiovascular Pathologiesmentioning
confidence: 99%
“…A recent study reported significantly higher levels of monomeric C-reactive protein (CRP)-positive MVs in patients with myocardial infarction compared with healthy controls [80] . In addition, elevated levels of circulating MVs have been associated with cardiovascular risk factors, including hyperten sion [15,32,52,100] , obesity [101,102] , cholesterol, and dyslipidemia [49,103] , as well as exposure to tobacco smoke [7] or air pollution [104,105] . An in vivo study also demonstrated that the levels of circulating endothelial-derived MVs and endothelial progenitor cell (EPC)-derived MVs are increased in diabetic animal models with ischemic stroke [106] .…”
Section: Mvs In Diabetic Macrovascular Complicationsmentioning
confidence: 99%
“…Procoagulant platelet-derived MVs [47,48] , monocytederived MVs [14] , and endothelial-derived MVs [49] are significantly increased in patients with diabetes, even in wellcontrolled DM without complications [50] and newly diagnosed T2DM [51] . In addition, patients with diabetes accompanied by hyperten sion [15,16,32,[52][53][54][55][56][57] , hyperlipidemia [58][59][60] , stable coronary disease [61] , angina with [62] or without [17] symptomatic episodes, myocardial infarction [49,63] , diabetic retinopathy, and nephropathy [33,64] have significantly increased levels of procoagulant MVs compared with those without diabetic complications. Therefore, elevated levels of MVs may be associated with the increased risk of thrombo-embolic diabetic complications.…”
Section: Mvs and Thrombosismentioning
confidence: 99%